Circulating and dietary advanced glycation end products and obesity in an adult population: A paradox of their detrimental effects in obesity - Turki Jalil, Abduladheem; Alameri, Ameer A.; Iqbal Doewes, Rumi; El-Sehrawy, Amr A.; Ahmad, Irfan; Ramaiah, Pushpamala; Kadhim, Mustafa M.; Kzar, Hamzah H.; Sivaraman, R.; Romero-Parra, Rosario Mireya; Ansari, Mohammad Javed; Fakri Mustafa, Yasser (Frontiers in Endocrinology, 2022)
Background: The detrimental role of AGEs against cardio-metabolic health has been revealed in several previous reports. However, the results of studies regarding the association between AGEs and obesity measurements are inconsistent. In the current meta-analysis, we aimed to quantitatively summarize the results of studies that evaluated the association between circulating and dietary AGEs with obesity measurements among the adult population. Methods: A systematic search from PubMed, Embase, and Scopus electronic databases until 30 October 2022 retrieved a total of 21429 observational studies. After duplicate removal, title/ abstract screening, and full-text reading by two independent researchers a final number of 18 manuscripts remained to be included in the meta-analysis. Results: Those in the highest category of circulating AGEs had ̴ 1.5 kg/m2 reduced BMI compared with those in the lowest AGEs category [weighted mean difference (WMD):-1.485; CI: -2.459, -0.511; P = 0.003]. While, a non-significant increase in BMI was observed in the highest versus lowest category of dietary AGEs (WMD: 0.864, CI: -0.365, 2.094; P= 0.186). Also, lower amounts of circulating AGEs in individuals with obesity versus individuals without obesity were observed (WMD: -57.220, CI: -84.290, -30.149; P <0.001). AGEs type can be considered as a possible source of heterogeneity. Conclusion: In the current meta-analysis, we observed an inverse association between circulating AGEs and body mass index among adults. Due to low study numbers, further studies are warranted to better elucidate these results.